Texas Instruments, Inc; It's Winning Strategies In Engineering The World - Balakrishnan, Balanaveenan (2008)
The objective of this case study is to enable Texas Instruments to remain competitive as the market leader in semiconductor manufacturing and continue to gain market share against their competitors.